Analisis Manajemen Perawatan Mesin Produksi Kemasan Plastik Spout dengan Metode Reliability Centered Maintenance (RCM) - Daniel Chrisnanda Septrian Putra; Etik Puspitasari (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Plastic packaging manufacturing company, X Corporation uses assembly machines to produce spout. In 2023, the assembly machine experinced a high frequency of downtime, which is 106 times with a total 190.5 hours. This research aims to analyze the machine maintenance management with the RCM method. Determination of critical components by FMEA, with an RPN value at very high level (> 200), four critical components are obtained, namely line feeder, transmission, electrical sensor, pneumatic. Calculation of reliability values using Weibull distribution. Then obtained the reliability value of line feeder component 0.5 when (t) 128 hours, transmission 0.5 when (t) 96 hours, electrical sensor 0.5 when (t) 184 hours, and pneumatic 0.5 when (t) 627 hours. Based on the reliability value, the line feeder maintenance schedule is determined every 5 days (max. inspection), 2 weeks (repair), 1 month (replace); transmission every 4 days (max. inspection), 4 weeks (repair), 2 months (replace); electrical sensor every 8 days (max. inspection), 5 months (repair), 10 months (replace); pneumatic every 28 days (max. inspection), 3 months (repair), 6 months (replace); overhaul at least once a year. The preventive maintenance cost in one year is Rp45,107,309.